The Council on Campus: The Experience of Vatican II at Boston College - O'Toole, James M. (The Catholic historical review, 2017)
This essay presents a case study of the reception and implementation of the reforms of the Second Vatican Council at one American Catholic university, Boston College. The college, one of the twenty-eight Jesuit institutions of higher education in the United States, entered the 1960s in the midst of several decades of programmatic expansion, but it was largely unprepared for the changes that would come in the Council's wake. Student religious practice had been relatively underdeveloped, and the teaching of theology had proceeded along very traditional lines. But by the time the Council concluded, the campus had embraced liturgical reform, most noticeably in the complete renovation of the student chapel. The inadequacies of the theology department were also recognized early, and a major remaking of the faculty and curriculum was undertaken, turning the discipline in a more clearly academic direction. Though accompanied by some controversy, these transformations were accomplished in short order, with a level of enthusiasm for change taking hold.